1974
DOI: 10.1073/pnas.71.8.3162
|View full text |Cite
|
Sign up to set email alerts
|

Sister Chromatid Exchanges, Indices of Human Chromosome Damage and Repair: Detection by Fluorescence and Induction by Mitomycin C

Abstract: Sister chromatid exchanges in chromosomes from human lymphocytes grown two replication cycles in medium containing 5-bromodeoxyuridine can be detected by fluorescence microscopy after staining with the Jisbenzimidazole dye 33258 Hoechst. These exchanges are mucbh more frequent than chronosome or chromatid breaks and appear to be partly but not entirely due to 5-broxpodeoxyuridine incorporation. Sister

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
10

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(93 citation statements)
references
References 24 publications
(18 reference statements)
4
79
0
10
Order By: Relevance
“…Sontakke YA (2008) 1 found that interchange exchange was the most common chromosomal aberration induced by mitomycin c and other chromosomal aberrations were associations of acrocentric association and attenuation of secondary constriction and agrees with the present study. Latt SA (1974) 28 observed significant increase in the SCE (sister chromatid exchange) with increase in concentration of mitomycin c. Finding of the above researchers corresponds with the present study. Brogger A (1973) 25 revealed a prevalence of attenuations, lateral extensions and exchanges in the secondary constrictions of chromosomes 1, 9, and 16 in the mitomycin c treated material and not with methylmetanesulphonate MMS.…”
Section: Interchange Exchange By Mitomycin Csupporting
confidence: 80%
“…Sontakke YA (2008) 1 found that interchange exchange was the most common chromosomal aberration induced by mitomycin c and other chromosomal aberrations were associations of acrocentric association and attenuation of secondary constriction and agrees with the present study. Latt SA (1974) 28 observed significant increase in the SCE (sister chromatid exchange) with increase in concentration of mitomycin c. Finding of the above researchers corresponds with the present study. Brogger A (1973) 25 revealed a prevalence of attenuations, lateral extensions and exchanges in the secondary constrictions of chromosomes 1, 9, and 16 in the mitomycin c treated material and not with methylmetanesulphonate MMS.…”
Section: Interchange Exchange By Mitomycin Csupporting
confidence: 80%
“…Likewise, the observation of SCE notably indicates effects of chemical mutagens and carcinogens on eukaryotic chromosomes. The first study dealing with this issue was carried out by Latt (1974) on human lymphocyte chromosomes treated with the bifunctional alkylating agent MMC that cross-links DNA. Additionally, Perry and Evans (1975) found that all direct-acting mutagens led to dramatically increased frequencies of SCEs in Chinese hamster ovary cells treated with 14 known or suspected mutagens/carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…This would inhibit DNA replication and probably might be the antitumor action of this drug. Despite the fact that MMC showed antitumor action, many reports proved that it may cause high frequency of chromosomal aberrations, sister chromatid exchanges and micronuclei formation (Latt 1974;Fauth et al 2000;Yogesh and Fulzele 2009). In this study, we used this antitumor-antibiotic drug to test the possible antimutagenic activity of concrete and absolute oils.…”
Section: Gc-ms Analysismentioning
confidence: 99%